[Crowd near] Afro-American Student Union booth (1988)
Wide view of the African American Student Union (AASU) booth in between two other booths, and the small crowd interacting with the three booths and walking along the sidewalk. The AASU booth sign advertises 'Chile Corn Chips ($1.50), Soda (60¢)'.